THE ILLUSTRATION GROW OF CONTAMINANT FUNGI AT WHITE BREAD BASED ON TEMPERATURE AND HUMIDITY (STIKes Mitra Keluarga, 2021)
Introduction: Food is a basic need for every living creature. Bread is one of the processed foods that is consumed by many people as a staple food substitute for rice. The shelf life of white bread is usually not more than a week or even just three days. The appearance of bread that is not suitable for consumption is indicated by the appearance of discoloration on the bread due to being overgrown with fungus. The fungus that grows on white bread can produce mycotoxins during the storage process. Food poisoning can cause symptoms such as nausea, vomiting, and diarrhea. Method: The purpose of this study was to determine the average percentage of white bread covered with contaminant fungi based on temperature and humidity. The method used is descriptive. Results: The results showed that white bread overgrown with contaminant fungi by steaming and not steaming which was placed at room temperature grew faster than white bread placed at refrigerator temperature. At room temperature (27°C - 30°C), contaminant fungi began to grow on the seventh day on white bread 1 and on the fourth day on white bread 2 with the steamed treatment, while for the non-steamed treatment the contaminant fungi began to grow on the fifth day. At refrigerator temperature (13°C - 16°C), white bread with steamed and unsteamed treatment was not covered with contaminant fungi. Conclusion: The conclusion of this study is that white bread overgrown with contaminant fungi at room temperature with steam treatment was 3.33% on the fourth to fifth day, and 66.6% on the seventh day. Bread covered with contaminant fungi at room temperature with treatment not steamed as much as 3.33% on the fifth to the seventh day. Researchers hope that future researchers can conduct this research by adding a microscopic examination method.